Vitrectomy with Air Endotamponade for Traumatic Cyclodialysis - Anan Wang; Zhenquan Zhao (Journal of Ophthalmology)
Background. Various techniques have been described for repairing cyclodialysis clefts, but there is no consensus regarding the optimal treatment. This study investigated the clinical efficacy of a novel surgical approach that is used to manage traumatic cyclodialysis. Methods. We prospectively enrolled 7 patients (7 eyes) with traumatic cyclodialysis of the concomitant lens and other vitreous diseases. Ultrasound biomicroscopy was used to diagnose cyclodialysis, and all eyes underwent pars plana vitrectomy with air endotamponade. The main outcome measures were postoperative anatomical success rates, best-corrected visual acuity (BCVA), and intraocular pressure (IOP). Results. All patients were male, and their age ranged from 46 to 64 years (mean: 54.3 years). After the surgical intervention, the extent of the cyclodialysis cleft ranged from 1 to 4 clock hours (mean: 2.3 clock hours) and the detached ciliary body of all cases was completely restored; the anatomical success rate was 100%. The BCVA significantly increased from 1.40 ± 0.49 to 0.42 ± 0.31 (P = 0.002). The IOP increased from 8.91 ± 1.77 to 14.67 ± 6.38, but the difference was not significant (P = 0.056). The postoperative IOP of most patients was temporarily elevated or lowered after surgery. At the last follow-up, there were still two abnormal cases, including one with ocular hypertension and one with hypotony. Conclusions. This study revealed that vitrectomy with air endotamponade is an effective and minimally invasive alternative surgical approach for small traumatic cyclodialysis clefts.